Medical data security for bioengineers - Singh, Butta, 1981-; Saini, Barjinder Singh, 1970-; Singh, Dilbag; Pandey, Anukul (Advances in bioinformatics and biomedical engineering book series., 2019)
"This book examines the issues facing medical data security in healthcare systems and applications. It also explores the advancements in engineering applications to healthcare technologies, biomedical information security and data privacy, and cloud computing technologies in healthcare"--Provided by publisher